Cobalt-Catalyzed Carbo- and Hydrocyanation of Alkynes via C–CN Bond Activation - Wang, Chang-Sheng; Yu, Yongqi; Sunada, Yusuke; Wang, Chen; Yoshikai, Naohiko (ACS catalysis, 2022)
Cobalt-catalyzed carbo- and hydrocyanation reactions of alkynes via C–CN bond cleavage of organic cyanides are reported. A low-valent cobalt–diphosphine catalyst generated by reduction with Zn promotes the arylcyanation of alkynes with trans-selectivity. By contrast, the addition of Zn(OTf)2 to this catalytic system not only accelerates the transformation but also switches the stereoselectivity, affording cis-arylcyanation products. The present catalytic systems prove to be effective for alkenylcyanation using alkenyl cyanides as well as for transfer hydrocyanation using propionitrile as the HCN surrogate. Experimental and computational studies on arylcyanation have been performed to gain insight into the reaction pathways, including the possible origin of the stereodivergence under cobalt and cobalt/zinc catalysis.